Infección herpética del aparato genital femenino detectada por citología - Campos Rey de Castro, Jorge (2024)
Eleven cases of herpeti colpocervicitis detected in a serie of 30.000 routine gynecological smears studied in 1973 and 1974, have been presented. Considering that the group of patients we have studied belong to medium socio-economic class and having no other references published locally we assume that the real incidence of this infection in the whole women population of this country is much higher than the 0.36 per thousand we found.  Only in one case the herpetic infection was suspected clinically; In another case the infection, was associated with adeno carcinoma of the cervix. The medium age of our cases was 30.8 years which is lower than the medium age of patients with dysplasia (36.3 years), carcinoma in situ (41.0 years) and infiltrating carcinoma of the cervix (47.3 years). We discuss the significance of the herpes virus as oncogenic factor in the pathogenesis of cancer of the cervix and the importance of cytological detection of the female genital tract herpetic infection at the end of pregnancy.